Number head together model integrated with Papuan local wisdom in digital technology-based mathematics learning media - Ainun Mardiah; Rizky Ekawaty Ahmad; Abu Bakar; Sulkipli M; Novanda Tamelab (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study aims to explore how the Numbered Heads Together (NHT) cooperative learning model, when combined with augmented reality (AR) media using Assemblr Edu and Papuan local wisdom, can improve elementary students’ understanding of geometry. Method: A quasi-experimental design was used with two groups: one taught using the integrated model and the other taught with conventional methods. Data were collected through geometry tests, classroom observations, and student questionnaires. The analysis focused on comparing students’ understanding and engagement in both groups. Findings: The integrated learning design helped students become more active, motivated, and collaborative. They showed better understanding of geometric concepts and were more confident in applying them to real-life and cultural contexts. The combination of cooperative learning, digital media, and local wisdom created a more engaging and meaningful learning experience. Significance: This study demonstrates that blending pedagogy, technology, and culture can make mathematics learning more relevant and accessible, especially in frontier and culturally diverse regions. The approach offers a model for teachers seeking to connect abstract mathematical ideas with students’ everyday experiences.